2016
DOI: 10.1007/s00248-016-0781-1
|View full text |Cite
|
Sign up to set email alerts
|

High Nutrient Concentration Can Induce Virulence Factor Expression and Cause Higher Virulence in an Environmentally Transmitted Pathogen

Abstract: Environmentally transmitted opportunistic pathogens shuttle between two substantially different environments: outside-host and within-host habitats. These environments differ from each other especially with respect to nutrient availability. Consequently, the pathogens are required to regulate their behavior in response to environmental cues in order to survive, but how nutrients control the virulence in opportunistic pathogens is still poorly understood. In this study we examined how nutrient level in the outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 58 publications
(51 reference statements)
0
35
0
Order By: Relevance
“…In contrast, while nutrient addition also led to improved bacterial replication compared to the baseline level, the growth between the low‐ and high‐nutrient environments did not differ. This result indicates that in addition to the increased outside‐host growth of the pathogen, increased nutrient availability is likely to promote bacterial virulence via virulence factor activation (Penttinen, Kinnula, Lipponen, Bamford, & Sundberg, ). Taken together, our results suggest that fluctuations in environmental nutrient conditions can have immediate effects on disease dynamics and outbreak severity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, while nutrient addition also led to improved bacterial replication compared to the baseline level, the growth between the low‐ and high‐nutrient environments did not differ. This result indicates that in addition to the increased outside‐host growth of the pathogen, increased nutrient availability is likely to promote bacterial virulence via virulence factor activation (Penttinen, Kinnula, Lipponen, Bamford, & Sundberg, ). Taken together, our results suggest that fluctuations in environmental nutrient conditions can have immediate effects on disease dynamics and outbreak severity.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the gut histology and availability niches change as the host ages, the initial "winners" will be reassembled, thereby resulting in a host stage-specific gut microbiota (Greenhalgh et al, 2016;Stephens et al, 2015;Xiong et al, 2018;Yan et al, 2016). Instead, water quality tends to be deteriorative and eutrophic over shrimp cultivation (Xiong et al, 2014;Yang et al, 2018), which stresses shrimp and increases the virulence of pathogens (Penttinen, Kinnula, Lipponen, Bamford, & Sundberg, 2016). In turn, shrimp relocate energy in response to pathogen invasion, thereby attenuating their filtering abilities.…”
Section: Ontogeny and Disease Effects On The Hostbacterial Colonizamentioning
confidence: 99%
“…Gut bacteria adjust their metabolism according to both the substances produced by other microbes and the nutrient supply, which may produce effects that influence metabolic and inflammatory pathways in the human body [31]. For instance, both human and animal studies have demonstrated that pathogens, pathobionts and other members of the microbiome can respond to a change in their environment (e.g.the presence of some emulsifiers; discussed later) by increasing expression of virulence factors [32][33][34], thereby increasing the pro-inflammatory potential of the microbiome Major changes in diet and subsequent changes in microbiota can, at least to some extent, be reversed within the same generation. However, recent studies in rodents have demonstrated that loss of microbiota diversity due to dietary changes can be transferred to later generations , with progressive loss of diversity [35].…”
Section: Factors That Promote Inflammation Through Diet-microbiome-homentioning
confidence: 99%
“…It is likely that abundance of accessible nutrients in the small intestine of animals signal large nutrient availability and sufficient resources to expand the bacteria's territory [32,46]. These effects could propagate further down the digestive system.…”
Section: Acellular Nutrients -A Major Shift In Our Dietsmentioning
confidence: 99%